Analysis of Childbirth Preparation Among Pregnant Women Using the Maternal and Child Health Handbook - Rury Narulita Sari; Nisa Ardhianingtyas; Fitra Riski Ayu Duana Putri (Health Dynamics, 2026)
Introduction: The Maternal Mortality Ratio (MMR) is a key indicator of public health and maternal healthcare quality. In Indonesia, the MMR declined to 144 per 100,000 live births in 2025, achieving the national strategic target of 183 per 100,000 live births. However, further reductions are needed to meet the 2030 Sustainable Development Goals (SDGs) target of 70 per 100,000 live births. The updated 2024 Maternal and Child Health Handbook supports pregnancy monitoring and birth preparedness. This study aimed to examine birth preparedness among pregnant women through the use of the Maternal and Child Health Handbook. Methods: This study employed a qualitative research method with a phenomenological approach. The study was conducted in the Candimulyo Village area, Madiun Regency, in March 2026. The study informants consisted of 12 pregnant women in their second and third trimesters who were attending prenatal check-ups. Data collection was conducted through in-depth interviews, followed by analysis involving data categorization, data presentation, and drawing conclusions. Results: The study results indicate that the majority of pregnant women make effective use of the Maternal and Child Health Handbook when reviewing birth preparations. Conclusions: The conclusion of this study is that the better a mother utilizes the Maternal and Child Health Handbook, the more effective her efforts to prepare for childbirth will be. It is recommended to seek support from healthcare professionals (midwives) and family members when preparing for childbirth by utilizing the Maternal and Child Health Handbook.